The additional act of 1834 and the autonomy of the provinces: a historical and legal analysis about the 1824 constitutional reform under the influence of liberal constitutionalism of the nineteenth century - Cabral Renovato Silva, Tito Lívio; Spellmann Cavalcanti de Farias, Samuel André (Revista Jurídica Portucalense, 2016)
This article aims to address, first, the historical and legal context of the First Empire, more precisely of the Empire constitutional process, from the Constituent Assembly of 1823, dissolved thereafter until the grant of the Constitution of 1824. It is mister analyze these facts, synthetically, to serve as a backdrop to address the political decentralization experiences and the first reform of the Empire Constitution during the Regency period, after the abdication of D. Pedro I, established by the Additional Act of 1834. The first reform the Constitution will be analyzed from the theory of constituent power, to evaluate innovation in the political situation of the country until their return with the Act Interpretation Act Additional 1840.